Between sunrise and sunset: formative meanings for the teaching work in early childhood education in cloudy times - Oliveira, Marta Regina Furlan de; Silva, Alex Sander da (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
In the profuse challenges of the contemporary context marked by the tensions and uncertainties of a time that devours everything, we aim to reflect on the need to (re) think the formative meaning of the teaching work for early childhood education with a view to humanizing the child. This text is linked to the post-doctoral research proposal presented to the Post-Graduate Program in Education at the Universidade do Extremo Sul Catarinense, UNESC, Criciúma, Santa Catarina, and that is being carried out from May to December 2021 with a CNPq scholarship - Senior Postdoctorate - 2020. Through the bibliographical survey about the interlocution among Childhood, Teacher Education, and Critical Theory of Society, it is necessary to welcome and minimize, through teacher training, the social and educational inequalities in defense of a childhood education that is attentive to the conditions of each educational community and that guarantees the democratic and humanizing processes of teaching.